2021
DOI: 10.18087/cardio.2021.12.n1558
|View full text |Cite
|
Sign up to set email alerts
|

The frequency and profile of drug treatment in subjects with dyslipidemias and cardimetabolic diseases in an urban russian population older then 55 years

Abstract: Aim      To analyze frequency and profile of the lipid-lowering therapy (LLT) in patients with dyslipidemia (DLP) and cardiometabolic diseases (CMD) in a population sample aged 55-84 years at the current time (2015–2017).Material and methods  Despite guidelines on DLP treatment and the availability of effective and safe lipid-lowering drugs, control of DPL in primary and secondary prevention of cardiovascular diseases (CVD) is insufficient. Knowledge of the level of pharmaceutical correction of DLP in the Russ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Early findings on drug therapy for atrial fibrillation, antihypertensive and lipid-lowering therapy in the studied population have previously been reported [ 20 , 21 , 22 ]. The present paper continues a systematic series of works on the pharmacotherapy of cardiometabolic diseases in the modern Russian population, using a population-based urban sample of older age persons in Novosibirsk.…”
Section: Introductionmentioning
confidence: 99%
“…Early findings on drug therapy for atrial fibrillation, antihypertensive and lipid-lowering therapy in the studied population have previously been reported [ 20 , 21 , 22 ]. The present paper continues a systematic series of works on the pharmacotherapy of cardiometabolic diseases in the modern Russian population, using a population-based urban sample of older age persons in Novosibirsk.…”
Section: Introductionmentioning
confidence: 99%
“…Te HAPIEE study (2002)(2003)(2004)(2005) showed relatively low awareness of diabetes (30.8% in males and 45.2% in females) and hypercholesterolemia (11.2% in males and 15.3% in females) in Russia compared with Poland, Lithuania, and the Czech Republic [3]. Several studies assessed the control of DM and high cholesterol [25][26][27], but we could not fnd Russian population-based studies focusing behavioral and health characteristics associated with the awareness.…”
Section: Introductionmentioning
confidence: 99%